2004
DOI: 10.1016/s0896-6273(04)00083-2
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation in HCN Channels Results from Reclosure of the Activation Gate

Abstract: Hyperpolarization-activated HCN channels are modulated by direct binding of cyclic nucleotides. For HCN2 channels, cAMP shifts the voltage dependence for activation, with relatively little change in the maximal conductance. By contrast, in spHCN channels, cAMP relieves a rapid inactivation process and produces a large increase in maximum conductance. Our results suggest that these two effects of cAMP represent the same underlying process. We also find that spHCN inactivation occurs not by closure of a speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
162
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(174 citation statements)
references
References 20 publications
11
162
0
1
Order By: Relevance
“…These findings most likely reflect a destabilization of the open state, causing local perturbations in conformation that could allow channels to close during depolarizations. This finding is similar to a proposed mechanism of current decay during long periods of activation proposed in spHCN channels (Shin et al, 2004) and in Kv4.2 (Dougherty et al, 2008), and is consistent with the finding that multiple pathways of current decay exist in other Kv1 channels, as was shown in Kv1.3 (Marom and Levitan, 1994). Though it represents a different conclusion, this result also appears to be consistent with observations of a shorter mean open time in single-channel analysis of homotetramers of Kv1.1 V408A as well as Kv1.1-Kv1.2 heterotetramers possessing the same mutation (D'Adamo et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…These findings most likely reflect a destabilization of the open state, causing local perturbations in conformation that could allow channels to close during depolarizations. This finding is similar to a proposed mechanism of current decay during long periods of activation proposed in spHCN channels (Shin et al, 2004) and in Kv4.2 (Dougherty et al, 2008), and is consistent with the finding that multiple pathways of current decay exist in other Kv1 channels, as was shown in Kv1.3 (Marom and Levitan, 1994). Though it represents a different conclusion, this result also appears to be consistent with observations of a shorter mean open time in single-channel analysis of homotetramers of Kv1.1 V408A as well as Kv1.1-Kv1.2 heterotetramers possessing the same mutation (D'Adamo et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…These arguments for distinct manifestations of channel inhibition are very similar to those proposed to account for different forms of activation induced by cAMP in two HCN channels (Shin et al, 2004), although in that previous model, an inactivated state was introduced to account for the somewhat anomalous behavior of a sea urchin HCN channel. In addition, an analogous situation obtains in the related cyclic nucleotide-gated (CNG) channels (Fodor et al, 1997).…”
Section: Allosteric Modulation Of Halothane-mediated Hcn Channel Inhisupporting
confidence: 63%
“…Previous mutagenesis studies demonstrated that the C terminus of HCN2 imparts substantially more basal inhibition to its core channel domains than does the C terminus of HCN1, accounting for its more hyperpolarized initial V 1/2 (Wainger et al, 2001;Wang et al, 2001); binding of cAMP to the C terminus acts to relieve basal inhibition, producing a more prominent depolarizing shift in V 1/2 of HCN2 channels. Based on a simplified model of HCN channel gating, adapted from Shin et al (2004), we suggest that differences in C-terminally mediated basal inhibition can lead primarily to a shift in V 1/2 or amplitude inhibition despite a common underlying inhibitory mechanism, i.e., stabilization of channel closed state.…”
Section: Allosteric Modulation Of Halothane-mediated Hcn Channel Inhimentioning
confidence: 99%
See 1 more Smart Citation
“…The current conducted by the HCN channels, I h , is rapidly and transiently modified by cAMP-mediated gating (Wang et al, 2002;Shin et al, 2004), altered channel phosphorylation (Zong et al, 2005;Poolos et al, 2006) and additional, undefined processes (Van Welie et al, 2004;Fan et al, 2005). Whereas these modulations are transient and reversible, transcriptional changes of HCN channel expression may last for months, alter neuronal firing patterns and contribute to a hyperexcitable hippocampal network (Chen et al, 2001;Brewster et al, 2002).…”
Section: Discussionmentioning
confidence: 99%